An Examination of the Efficiency of Cassava Marketing in East Lampung Regency, Lampung Province, Indonesia - Zakaria, Wan Abbas; Indah, Lidya Sari Mas; Endaryanto, Teguh; Seta, Amanda Putra; Sari, Dewi Mulia; Hermawan, Dedy (Jurnal AGRISEP, 2024)
Cassava is a strategic commodity that has an influence on the stability of food security and drives industries from small to large scale and from upstream to downstream.  Despite the potential and opportunities for developing cassava commodities in Lampung Province, the problems and challenges, especially those related to cassava marketing, are still relatively large. This research was conducted in Labuhan Ratu VI Village, Labuhan Ratu District, East Lampung Regency, Lampung Province in October 2020 - July 2021.  The sampling method used was the snowball method.  The snowball method is very appropriate to use in research on the topic of trade because it provides a complete description of the characteristics and conditions of marketing channels, the existing conditions of marketing institutions, and the effectiveness of existing trade channels.  The research was conducted employing a survey method, and by simple random sampling involving 147 respondents of cassava farmers. The results revealed that cassava marketing consists of 2 channels. Farmer share channel I and II respectively 74% and 86%, while  the marketing efficiency value (EP) marketing channel I and II respectively 13.04 % and 10.35%. These results show that marketing channel II is more efficient than marketing channel I because it has a high farmer share and marketing efficiency with a small percentage.  This is because in marketing channel II farmers directly sell their cassava to the factory and marketing costs are low.  Therefore, farmers are advised to market their products through marketing channel II.